Intricacies, intersections and interconnections: remembrance in Paris according to Julián Ríos - S (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Can the deceased live on in a city through memories? This is one of the questions raised by Julián Ríos in his 2019 Puente de Alma. Woven around Princess Diana’s accidental death in Paris, the Spanish author’s novel cultivates her memory, ambling through a shattered city of ghosts. He takes a closer look at the French capital, recasting its symbols as post-mortem forms of life, all the while redrawing, redefining and “re-viewing” its topography.
Keywords: Julián Ríos; Puente de alma; City; Signs; Ghosts